Factoring in weather variation to capture the influence of urban design and built environment on globally recommended levels of moderate to vigorous physical activity in children. Issue 11 (30th November 2015) - Katapally, Tarun Reddy; Rainham, Daniel; Muhajarine, Nazeem
Abstract : Objectives: In curbing physical inactivity, as behavioural interventions directed at individuals have not produced a population-level change, an ecological perspective called active living research has gained prominence. However, active living research consistently underexplores the role played by a perennial phenomenon encompassing all other environmental exposures—variation in weather. After factoring in weather variation, this study investigated the influence of diverse environmental exposures (including urban design and built environment) on the accumulation of globally recommended moderate to vigorous physical activity levels (MVPA) in children. Design: This cross-sectional observational study is part of an active living initiative set in the Canadian prairie city of Saskatoon. As part of this study, Saskatoon's neighbourhoods were classified based on urban street design into grid-pattern, fractured grid-pattern and curvilinear types of neighbourhoods. Moreover, diverse environmental exposures were measured including, neighbourhood built environment, and neighbourhood and household socioeconomic environment. Actical accelerometers were deployed between April and June 2010 (spring-summer) to derive MVPA of 331 10–14-year-old children in 25 1-week cycles. Each cycle of accelerometry was conducted on a different cohort of children within the total sample and matched with weather data obtained from Environment Canada. Multilevel modelling using Hierarchical Linear and Non-linear Modelling software was conducted by factoring in weather variation to depict the influence of diverse environmental exposures on the accumulation of recommended MVPA. Results: Urban design, including diversity of destinations within neighbourhoods played a significant role in the accumulation of MVPA. After factoring in weather variation, it was observed that children living in neighbourhoods closer to the city centre (with higher diversity of destinations) were more likely to accumulate recommended MVPA. Conclusions: The findings indicate that after factoring in weather variation, certain types of urban design are more likely to be associated with MVPA accumulation.